Primary Breast Angiosarcoma: A Case Report - Bozkurt, Birkan; Tokaç, Mehmet; Yıldırım, Muat Baki; Kılıç, Mehmet; Hücümenoğlu, Sema (Fırat University, 2012)
The primary angiosarcoma of the breast is a tomor which is seen rarely. The sarcomas are seen less than 1% in the breast cancers. Angiosarcoma is a rarely mesenchymal tumor which is seen most common in the breast, also in the heart, pericardium, liver, skin, bone and soft tissues. Diagnosis is made by biopsy. Mastectomy is applied during the treatment. The usefulness of chemotherapy and radiotherapy should be discussed. In this report, a 31-year-old woman with primary breast angiosarcoma is presented with literature reviews.

Memenin primer anjiyosarkomu nadir görülen bir tümördür. Sarkomlar, meme kanserleri içinde %1'den daha az görülmektedir. Anjiosarkom, en sık memede olmak üzere kalp, perikard, karaciğer, deri, kemik ve yumuşak dokularda görülen nadir bir mezenkimal tümördür. Tanı biyopsi ile konur. Tedavide mastektomi uygulanır. Kemoterapi ve radyoterapinin faydası tartışmalıdır. Burada primer meme anjiyosarkomu olan 31 yaşında kadın hasta literatür bilgileri eşliğinde sunulmaktadır.
Memenin Pirmer Anjiyosarkomu: Olgu Sunumu